Phenomenon of mesenchymal islet formation from rat marrow cells in vitro - V. P. Shakhov; O. V. Kokarev; S. V. Popov; S. A. Afanasyev; A. N. Baikov (Бюллетень сибирской медицины, 2004)
An attempt to check experimentally the possibility of structure functional units existence in mesenchymal cells, similar to hemopoetic and erythroblastic islets, has been made. Experiments on long (in vitro) cultivation of adhesive rat marrow elements have been made.It has been found that from the 6 day of observation there were specific cell formations with islet-like structure in the culture. An epitelioid cell surrounded by round elements was situated in the center. Up to 12-14 days the number of mesenchymal islets reached its maximum (up to 46,0 ⋅ 106 cells), after that it decreased gradually and up to 24 days it almost disappeared. The islets were a part of mesenchymal colonies.The authors suppose that these formations are structure functional units of mesenchymopoiesis where proliferation and differentiation processes of mesenchymal stem cells and their closest scions proceed.